2015
DOI: 10.3389/fnhum.2015.00265
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Brain Stimulation: An Interventional Tool for Enhancing Behavioral Training after Stroke

Abstract: Stroke is the leading cause of disability among adults. Motor deficit is the most common impairment after stroke. Especially, deficits in fine motor skills impair numerous activities of daily life. Re-acquisition of motor skills resulting in improved or more accurate motor performance is paramount to regain function, and is the basis of behavioral motor therapy after stroke. Within the past years, there has been a rapid technological and methodological development in neuroimaging leading to a significant progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 159 publications
1
59
0
4
Order By: Relevance
“…Unlike the pharmacological manipulation of tonic GABA in rodent models of stroke, which specifically manipulate excitatory neurons and preferentially those that have been impacted by stroke,5 tDC and TMS more grossly affect all of the brain tissue in the electrical or magnetic field, and induce many distinct types of cortical circuits 55. Nonetheless, small‐scale studies indicate that excitatory tDC or TMS over the ipsilesional hemisphere in stroke, or inhibitory tDC over the contralateral hemisphere, may improve recovery after stroke 55. Larger‐scale trials are under way for this application 56, 57…”
Section: The Suffered Is the Learnedmentioning
confidence: 99%
“…Unlike the pharmacological manipulation of tonic GABA in rodent models of stroke, which specifically manipulate excitatory neurons and preferentially those that have been impacted by stroke,5 tDC and TMS more grossly affect all of the brain tissue in the electrical or magnetic field, and induce many distinct types of cortical circuits 55. Nonetheless, small‐scale studies indicate that excitatory tDC or TMS over the ipsilesional hemisphere in stroke, or inhibitory tDC over the contralateral hemisphere, may improve recovery after stroke 55. Larger‐scale trials are under way for this application 56, 57…”
Section: The Suffered Is the Learnedmentioning
confidence: 99%
“…Non-invasive brain stimulation techniques are frequently used and studied for their potential applications in physical medicine and rehabilitation (Hoyer and Celnik, 2011;Adeyemo et al, 2012;Wessel et al, 2015). However, rTMS and tDCS are not comfortable for subjects submitted to these techniques (Hardwick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of behavioral training and non-invasive brain stimulation was also shown to present a new adjuvant in the treatment of neurological patients after brain injury (Wessel et al 2015). Using transcrancial direct current stimulation (tDCS), it could recently be demonstrated that episodic memory retrieval is dependent from activity during the encoding phase (Zwissler et al 2014) and that cognitive training of working memory is superior if applied ''online'' (tDCS during performance) in contrast to priming (tDCS before performance) (Martin et al 2014).…”
Section: Perspectivesmentioning
confidence: 99%